“Parental Meta-Emotion as a Mediator Between Perfectionism and Self-Handicapping in Adolescents”: “Parental Meta-Emotion, Perfectionism and Self-Handicapping in Adolescents” - Kheyrdoust , Shokoufeh; Kord Tamini, Bahman (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: This study was conducted to investigate the parental meta-emotion as a mediator between perfectionism and self-handicapping in adolescents of high school students in Zahedan City, Iran. Methods and Materials: The statistical population of this study consisted of all high school students in Zahedan in the academic year 2023-2024 and one of their parents (180 participants), of whom 180 adolescents (91 girls, 89 boys) were selected as the research sample by multi–stage cluster sampling. Participating parents answered the Kehoe (2006) Parents’ Meta-Emotion Philosophy Questionnaire, and their children answered two scales, Frost’s (1990) Multi-dimensional Perfectionism, and Jones and Rhodewalt’s (1982) Self–Handicapping Scale. The data were analyzed using Pearson’s correlation coefficient in SPSS–2 and path analysis through Smart PLS–4 software. Findings: The findings indicated that parental meta–emotion displayed a significant positive correlation with perfectionism (r= .30, p< .01) and a significant negative correlation with self-handicapping (r= -.14, p< .05). A substantial positive relationship existed between perfectionism and self–handicapping (r= .46, p< .01). The results indicated that parental meta–emotion had a significant effect on self–handicapping (Beta= -.413, t= 14.00, p= .0001). Perfectionism had a significant positive effect on parental meta–emotion (Beta= .503, t= 20.94, p= .0001). Perfectionism had a significant positive effect on self–handicapping (Beta= .728, t= 48.43, p= .0001). The indirect effect of perfectionism via the parental meta–emotion on self–handicapping (Beta= -.208, t= 12.10, p= .0001) was significant. The results indicated that parental meta-emotion significantly negatively affected self-handicapping, whereas perfectionism had a significant positive direct effect on both parental meta-emotion and self–handicapping. The findings further revealed that parental meta-emotion played a significant mediating role in the relationship between perfectionism and self–handicapping in adolescents. Conclusion: According to the results, it is concluded that parental meta-emotion is a significant mediator between perfectionism and self–handicapping in adolescents, and accordingly, it is recommended to adopt appropriate plans to regulate parental meta–emotion in adolescents.